A lithium supplement coating and its preparation method and application

By using organic lithium salt supplementary materials coated with carbon source in lithium-ion batteries, combined with phase change materials and adhesives, a lithium supplementary coating that can stably release active lithium is formed, which solves the problem of irreversible loss of active lithium in lithium batteries, achieves long-term effectiveness and stability, and improves the cycle life and performance of the battery.

CN119764620APending Publication Date: 2025-04-04SHENZHEN FAYMO TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411956501.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have irreversible losses of active lithium during the first charging process, resulting in low efficiency of Coulomb, reduced capacity and energy density, and it is difficult for traditional prelithiation technology to achieve long-term effectiveness and stability.

Method used

A lithium supplement coating including lithium supplement material, phase change material and binder is adopted. The lithium supplement material consists of an organic lithium salt with the structural formula LixCyOz and a carbon source coated thereon. The conductive and dispersibility are improved through the carbon source coating structure to achieve stable release of active lithium.

Benefits of technology

This technology can continuously and stably replenish lithium during the entire application of lithium batteries, reduce the attenuation rate of battery circulation capacity, and improve long cycle life and performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216001750000131
    Figure BDA0005216001750000131
  • Figure BDA0005216001750000151
    Figure BDA0005216001750000151
Patent Text Reader

Abstract

A lithium replenishing coating and its preparation method and application are intended to overcome the defects of using lithium powder as lithium replenishing material in the lithium replenishing coating used in the existing pre-lithiation technology, such as increased difficulty in the preparation process of the lithium replenishing coating and failure to achieve long-term and stable lithium replenishment of lithium batteries. The lithium replenishing coating comprises: a lithium replenishing material, a phase change material and an adhesive; the lithium replenishing material comprises: a lithium replenishing agent and a carbon source for the lithium replenishing material coated on the lithium replenishing agent to improve the conductivity of the lithium replenishing material; the lithium replenishing agent comprises: a lithium replenishing agent with a structural formula of Li x C y O z An organic lithium salt, wherein: 1<X<5, 0<Y<8, 2<Z<12; the mass ratio of the lithium replenishing agent and the carbon source for the lithium replenishing material is 1:(0.05~0.25); the lithium replenishing material used in the present invention is a structure in which the carbon source for the lithium replenishing material covers the organic lithium salt, which can ensure that when applied to a lithium battery, the active lithium can be released continuously and stably, and the organic lithium salt can stably exist in the air and an organic solvent, and is easy to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium supplement coating and a preparation method and application thereof. Background Art

[0002] At present, in the application process of lithium-ion batteries, there is inevitably the problem of active lithium loss: during the first charging process of lithium-ion batteries, the electrolyte is reduced and decomposed on the surface of negative electrode materials such as graphite to form a layer of solid electrolyte interface film (SEI). However, the formation of this SEI film will cause the consumption of active lithium in the positive electrode. This process is irreversible and not only occurs during the first cycle of charging and discharging, but also persists with the long-term cycle of the battery. This not only leads to a low coulombic efficiency in the first cycle, but also reduces the capacity and energy density of the lithium-ion battery.

[0003] At present, the pre-lithiation technology is mainly used to compensate for the irreversible capacity loss of active lithium in the initial stage and during the cycle of lithium batteries. The pre-lithiation technology can compensate for the active lithium loss of the battery by introducing additional active lithium into the battery. The pre-lithiation methods mainly include positive electrode lithium replenishment, negative electrode lithium replenishment, and diaphragm lithium replenishment. The Chinese patent "Negative Electrode Lithium Replenishment Plate and Its Preparation Method and Application" with publication number CN115036507A solves the above problems by replenishing lithium at the negative electrode. The negative electrode lithium replenishment plate includes: a negative electrode current collector, a negative electrode active material layer and a lithium replenishment coating. The lithium replenishment coating includes: lithium powder, a binder and a phase change material. The lithium is replenished by lithium powder, and the phase change material absorbs the heat generated during the lithium replenishment process. However, it has the following defects: (1) The use of highly active lithium powder has great safety hazards and needs to be used under specific conditions and measures, which increases the preparation process of the lithium replenishment coating. (2) As a lithium source, lithium powder decomposes and releases active lithium, which makes up for the irreversible loss of active lithium caused by the growth of SEI film and can replenish active lithium during the first charging of lithium-ion batteries. However, the release rate of active lithium from lithium powder is relatively fast, which can only meet the initial lithium replenishment and the early cycle lithium replenishment of lithium batteries. After the active lithium is released, it cannot continue to replenish lithium with the continued use of lithium batteries, and the long-term and stable lithium replenishment of lithium batteries cannot be achieved, and thus a lithium battery with long cycle life and stability cannot be obtained. Summary of the invention

[0004] The present invention overcomes the defects of the prior art in which lithium replenishing coatings for pre-lithiation technology use lithium powder as lithium replenishing material, such as increased difficulty in the preparation process of the lithium replenishing coatings; although the active lithium can be released relatively quickly, the long-term effectiveness and stability of lithium replenishment of lithium batteries cannot be achieved, and a lithium replenishing coating and a preparation method and application thereof are provided.

[0005] The technical solution adopted by the present invention to achieve the first invention objective is: a lithium supplement coating, comprising: a lithium supplement material, a phase change material and a binder; the lithium supplement material comprises: a lithium supplement agent and a carbon source for the lithium supplement material coated on the lithium supplement agent; the lithium supplement agent comprises: a structural formula of Li x C y O z Organic lithium salt, structural formula Li x C y O z In the invention, 1<X<5, 0<Y<8, 2<Z<12; the carbon source for lithium supplement material is a carbon source capable of improving the conductivity of lithium supplement material; the mass ratio of the lithium supplement agent and the carbon source for lithium supplement material is: 1:(0.05~0.25).

[0006] The beneficial effects of the technical solution are as follows: (1) in the lithium replenishing coating, the lithium replenishing agent is coated by the lithium replenishing material with a carbon source, thereby obtaining a lithium replenishing material coated with a carbon source. When the lithium replenishing material with this coating structure is applied to a lithium battery, active lithium can be released continuously and stably, thereby ensuring that a continuous and stable lithium replenishing effect can be obtained during the entire application process of the lithium battery, effectively reducing the attenuation rate of the battery cycle capacity, and obtaining a lithium battery with a long cycle life and stable performance;

[0007] (2) The carbon source for lithium supplement material coated on the lithium supplement agent can improve the conductivity of the lithium supplement material, promote the diffusion rate of lithium ions in the material, and thus improve the chemical properties of the lithium battery; the application of the carbon source for lithium supplement material also improves the dispersibility of the lithium supplement material, which is conducive to forming a finer lithium supplement slurry, improving the uniformity of the lithium supplement coating, and thus facilitating the application of the lithium supplement coating;

[0008] (3) The lithium replenishing agent in the lithium replenishing material includes a structural formula of Li x C y O z Organic lithium salts (1<X<5, 0<Y<8, 2<Z<12, this type of organic lithium salt can exist stably in air and organic solvents, is easy to use, and the difficulty of preparing the lithium-replenishing coating is significantly reduced compared to lithium powder as a lithium-replenishing agent;

[0009] (4) The lithium replenishing material of the present invention can be used in the preparation process of the water system. The lithium replenishing coating conductive slurry can be obtained by simple mixing, stirring and dispersing. Compared with the lithium powder used as a lithium replenishing agent, which needs to be applied in a specific solvent, it is environmentally friendly and has a relatively low cost.

[0010] Furthermore, in parts by weight, the lithium-replenishing coating includes: 20-30 parts of lithium-replenishing material, 10-20 parts of phase change material and 2-10 parts of adhesive. The phase change material can be selected from: organic phase change material, inorganic phase change material, organic-inorganic composite phase change material, etc. The binder is an aqueous binder, including one or a mixture of sodium alginate, guar gum, polyacrylic acid, polyacrylonitrile, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber emulsion and carboxymethyl cellulose. When preparing the slurry of the lithium-replenishing coating, it also includes: 300-500 parts of solvent, and the solvent is generally selected from: deionized water or anhydrous ethanol, preferably deionized water.

[0011] Preferably, the lithium supplement agent further comprises: a lithium supplement agent auxiliary dispersant; the lithium supplement agent auxiliary dispersant is: lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose; the mass ratio of the organic lithium salt to the lithium supplement agent auxiliary dispersant is 1:(0.005-0.025). The use of the lithium supplement agent auxiliary dispersant can help the organic lithium salt to disperse in the solvent, and is conducive to the dispersion of the organic lithium salt. The lithium supplement agent auxiliary dispersant is selected as lithium carboxymethyl cellulose, which can promote the dispersion of the organic lithium salt and achieve the purpose of lithium supplementation.

[0012] The organic lithium salt used in the present invention is an organic lithium salt that can stably exist in air and organic solvents. The preferred organic lithium salt is one or more of Li2C2O4, Li2C4O4, Li2C3O5, Li2C4O6, and Li2C6O6. The more preferred organic lithium salt is crystalline lithium squarate Li2C2O4.

[0013] In the lithium supplement material of the present invention, the carbon source used for the lithium supplement material is preferably: a carbon source containing a sulfonic acid group, which realizes the hydrophilicity of the lithium supplement material, facilitates its uniform dispersion, and improves the conductivity, is coated on the outer layer of the lithium supplement agent, improves the electrochemical activity of the lithium supplement agent, and reduces the decomposition potential. When the selected carbon source for the lithium supplement material is a sulfonated carbon source, the thermal stability of the preferred carbon source for the lithium supplement material is 180°C to 260°C, which is easy to use.

[0014] In order to further improve the properties of lithium supplement materials, the preferred carbon source for lithium supplement materials is a carbon source compounded with an organic carbon source containing sulfonic acid groups and carbon nanotubes in a ratio of 1: (0.15-0.5), such as a carbon source compounded with asphalt containing sulfonic acid groups and carbon nanotubes. The conductivity of carbon nanotubes is better than that of organic carbon sources containing sulfonic acid groups, but carbon nanotubes are not easy to disperse, resulting in the inability to effectively exert their conductivity. Organic carbon sources containing sulfonic acid groups have excellent hydrophilicity, and compounding with carbon nanotubes can effectively improve the hydrophilicity and dispersibility of carbon nanotubes, and also increase the conductivity of organic carbon sources containing sulfonic acid groups; and, compounding organic carbon sources containing sulfonic acid groups and carbon nanotubes can also form a better conductive network, so compounding carbon sources containing sulfonic acid groups and carbon nanotubes can significantly obtain carbon sources for lithium supplement materials with improved conductivity.

[0015] The conductivity of the carbon source used in the lithium supplement material is improved, and the conductivity of the lithium supplement material is improved accordingly. The improved conductivity reduces the internal resistance, and the transmission speed of lithium ions in the lithium battery is also increased accordingly, the charging and discharging speed of the lithium battery is improved, and the cycle life is increased.

[0016] The preferred particle size D50 of the carbon source for lithium supplementing material is a nanoscale carbon source. Nanoscale carbon sources have better properties and are beneficial to the application of lithium batteries. The preferred particle size D50 of the carbon source for lithium supplementing material is 50-100nm, and the further preferred particle size is 15-60nm.

[0017] In the lithium replenishing coating of the present invention, the phase change material used is preferably: a phase change microcapsule with a coating structure, and the phase change microcapsule includes: an organic phase change material with a phase change temperature of 25-60°C and a carbon source for a phase change material coated on the organic phase change material; the carbon source for the phase change material is a carbon source that can improve the conductivity of the phase change material; the mass ratio of the organic phase change material and the carbon source for the phase change material is: 1: (0.5-1). By introducing a carbon source to construct a conductive network, good conductive properties are obtained, and hydrophilic properties are also given to the phase change material. In addition, the use of phase change microcapsules to replace a single phase change material in the lithium replenishing coating improves the compatibility of the phase change material. In addition, because the outer layers of the lithium replenishing material and the phase change microcapsule are both coated with a carbon source, the compatibility between the two is further improved, which is conducive to the uniform mixing between the lithium replenishing material and the phase change microcapsule, and the obtained lithium replenishing slurry is more delicate, thereby obtaining a more uniform lithium replenishing coating. Due to the excellent compatibility between lithium-replenishing materials and phase change microcapsules, when preparing lithium-replenishing coatings, only a small amount of dispersant and binder needs to be added. Through simple mixing and stirring, a uniform and fine lithium-replenishing slurry can be dispersed and obtained. The preparation process of lithium-replenishing coatings is simpler and more environmentally friendly.

[0018] Preferred organic phase change materials are: one or two of alkane phase change paraffin, lauric acid, polyethylene glycol, stearic acid, n-octadecyl alcohol, palmitic acid, and the above.

[0019] In order to further improve the application advantages of phase change microcapsules, the preferred phase change microcapsules are nitrogen pyridine modified phase change microcapsules, wherein the mass ratio of organic phase change material, carbon source for phase change material, and nitrogen pyridine is: 1: (0.5-1): (0.015-0.025). By modifying the phase change microcapsules (carbon source coated organic phase change material) with multifunctional nitrogen pyridine, using multifunctional nitrogen pyridine as a crosslinking agent to partially crosslink with the carboxyl-containing part of the system, including the dispersant for lithium supplement: carboxymethyl cellulose-Li, and the carboxyl group in some binders to achieve a variety of complex crosslinked network structures, and the strong electron donor at the inter-position of the pyridine ring N atom, electrophilic substitution reaction occurs, and the polymer binder acts, which can effectively improve the wear resistance and electrolyte immersion resistance of the lithium supplement coating; and when the lithium supplement coating is applied to the lithium battery separator, it can also improve the adhesion between the lithium supplement coating and the separator.

[0020] In order to further improve the compatibility of lithium supplement materials and phase change materials, the preferred carbon source for phase change materials and the carbon source for lithium supplement materials can be selected from the same type of carbon source, such as: a carbon source containing sulfonic acid groups, and more preferably a carbon source formed by compounding an organic carbon source containing sulfonic acid groups and carbon nanotubes in a ratio of 1: (0.15-0.5). The thermal stability of the carbon source for phase change materials is preferably 180°C to 260°C; the particle size D50 is a nanoscale carbon source, preferably D50 is 50-100nm, and the more preferred particle size D50 is 15-60nm. The same type of carbon source is used for lithium supplement materials and phase change materials, and the preparation process is also simpler and the compatibility is better.

[0021] By using the coordinated effect of phase change microcapsules and lithium supplement materials, an excess of active lithium supplement agents are preloaded, and the heat generated during the charging and discharging process of lithium-ion batteries is used to generate a porous structure in the lithium supplement coating through the phase change of organic phase change materials, so that the lithium supplement agent can continuously provide active lithium ions, which can not only provide a lithium source during the first charge, but also achieve a reasonable release of the lithium supplement agent, effectively compensate for the lithium ions consumed by the formation of the SEI film of the negative electrode material in the early stage, and supplement the lithium consumption during the cycle process, thereby improving the first coulomb efficiency and cycle life of the lithium-ion battery. At the same time, by coating the lithium supplement material with phase change materials, the contact between the lithium supplement agent and the electrolyte can be effectively reduced, avoiding the possibility of side reactions between the residual alkali on the surface of the lithium supplement material and the electrolyte.

[0022] The technical solution adopted by the present invention to achieve the second invention objective is: the preparation method of the lithium supplement coating described in more than one technical solution comprises the following steps:

[0023] S1, preparing the lithium supplement material;

[0024] S2, preparing the phase change material;

[0025] S3, mixing the lithium supplement material obtained in step S1, the phase change material obtained in step S2, a binder and a solvent, and stirring at high speed to obtain a lithium supplement slurry;

[0026] S4, coating the lithium replenishing slurry obtained in step S3 on the lithium replenishing coating carrier, and obtaining the lithium replenishing coating after drying.

[0027] In the preparation method of the present invention, the lithium supplement material and the phase change material prepared in steps S1 and S2 are both materials coated with a carbon source.

[0028] Wherein, in the step S1, the lithium supplement material is prepared by the following steps:

[0029] S1.1, preparing the carbon source for the lithium supplement material;

[0030] S1.2, preparing a lithium supplement solution containing a lithium supplement agent;

[0031] S1.3, adding the carbon source for lithium supplementing material obtained in step S1.1 to the lithium supplementing solution containing the lithium supplementing agent in step S1.2, stirring to disperse and dissolve the carbon source for lithium supplementing material, to obtain a lithium supplementing agent-lithium supplementing material carbon source solution;

[0032] S1.4, recrystallizing the lithium supplement in the lithium supplement-lithium supplement material carbon source solution obtained in step S1.3 to obtain a lithium supplement-lithium supplement material carbon source composite material, namely, the lithium supplement material.

[0033] Furthermore, in the preparation step S1.2 of the lithium supplement material, a lithium supplement solution containing a lithium supplement agent is prepared by the following method: an organic lithium salt and a lithium supplement agent auxiliary dispersant are taken in a ratio of 1: (0.005-0.015), dissolved in water, and prepared into a lithium supplement solution containing a lithium supplement agent with a concentration of 10-25%. When preparing the lithium supplement solution, generally a stirring speed of 800-2500r / min is selected at room temperature for 2-6h. In step S1.3, in order to ensure that a lithium supplement agent-lithium supplement material carbon source solution with better properties is obtained, preferably, after the lithium supplement material carbon source is dispersed and dissolved by stirring, stirring and dispersing is continued for 0.5-2h.

[0034] In the preparation process of the lithium replenishing coating, a lithium replenishing slurry needs to be prepared first. In the step 3, the lithium replenishing slurry includes, by weight, 20 to 30 parts of lithium replenishing material, 10 to 20 parts of phase change material, 2 to 10 parts of adhesive and 300 to 500 parts of solvent. The lithium replenishing slurry is prepared by high-speed stirring at a stirring speed of 1000-2500 r / min for 1-3 hours.

[0035] In the step S2, the phase change material is prepared by using supercritical fluid technology, and the preparation method comprises the following steps: S2.1, adding an organic phase change material and a carbon source for phase change material into a pressure and temperature controllable reactor, and heating the organic phase change material to melt; then introducing a supercritical fluid reaction medium, at 40-80°C and a pressure of 7.5-20Mpa, to obtain a phase change microcapsule suspension of the organic phase change material coated with the carbon source for phase change material;

[0036] S2.2. Prepare the desired phase-change microcapsules by using the phase-change microcapsule suspension obtained in step S2.1 through the method of step S2.2.1 or S2.2.2:

[0037] The step S2.2.1 is: subjecting the phase change microcapsule suspension obtained in step S2.1 to rapid cooling and pressure relief to obtain phase change microcapsule powder;

[0038] The step S2.2.2 is to spray the multifunctional nitrogen pyridine solution into the phase change microcapsule suspension obtained in step S2.1, stir and mix, and then quickly cool and release the pressure to obtain nitrogen pyridine modified phase change microcapsules.

[0039] In the above method for preparing phase change material using supercritical fluid technology: in step S2.1, after the supercritical fluid reacts, the pre-expansion temperature is 40°C; in step S2.2.2, after the nitrogen pyridine solution is sprayed, the stirring and mixing time is generally 0.5 to 1 hour.

[0040] In the above method of preparing phase change materials using supercritical fluid technology, the preferred supercritical fluid reaction medium is CO2. Supercritical CO2 fluid has solubility and good fluidity. From the perspective of rapid changes in fluid mechanics and thermodynamic properties, supercritical CO2 fluid technology has the advantages of rapid reaction, no solvent residue and environmental protection. The obtained phase change microcapsules also have the advantages of small particles, uniform size, controllable size, etc., and have significant advantages such as.

[0041] The phase change material is in liquid state when heated, and the carbon source for the phase change material rapidly expands in the supercritical reaction medium, disperses separately and then mixes with each other, achieving the effect of uniform mixing and coating under solvent-free conditions. The carbon source for the phase change material gives the phase change material conductivity and a certain hydrophilicity. If a small molecule nitrogen pyridine solution is sprayed during the supercritical fluid reaction, it uses the carbon source for the phase change material as a nucleation point and is embedded in the mixed system of the carbon source for the phase change material and the phase change material. Through the sudden drop in pressure and temperature, it can be rapidly solidified and precipitated with the phase change material to obtain nitrogen pyridine-modified phase change microcapsules.

[0042] In the preparation method of the lithium supplement coating of the present invention, taking the carbon source for lithium supplement material and the carbon source for phase change material as a composite carbon source of sulfonated asphalt and carbon nanotubes as an example, the preparation can be carried out by the following method:

[0043] a1. Dissolution-compounding: Using sulfonated asphalt powder as raw material and deionized water as solvent, dissolving and preparing a sulfonated asphalt aqueous solution with a solid content of 5% to 30%; then adding carbon nanotubes at a compounding ratio of 1:(0.15 to 0.5) of solid content, and obtaining a compounded carbon source dispersion after high-speed dispersion and stirring for 1 to 2 hours;

[0044] a2. Sand milling: placing the carbon source dispersion prepared in step a1 in a sand mill, using zirconium beads with a diameter of 0.05 to 1 mm as sand milling media, and sand milling at a sand milling speed of 1000 to 2500 r / min for 0.25 to 2 h to obtain a composite carbon source sand mill slurry;

[0045] a3. Purification: The composite carbon source sand-ground slurry obtained in step a2 is sieved by sieving or directly centrifuged to collect the carbon source purified liquid with a particle size D50 of nanometer level.

[0046] a4. Spray drying: Place the purified nano carbon source solution obtained in step a3 into a spray dryer at 120-180° C. at a rate of 5-15 mL / min to collect the nano carbon source particles.

[0047] The technical solution adopted by the present invention to achieve the third invention objective is: a lithium-ion battery separator, comprising: a separator substrate and a lithium replenishing coating arranged on one side or both sides of the separator substrate; the lithium replenishing coating is the lithium replenishing coating described in the above technical solution.

[0048] Generally, when the lithium supplement coating is disposed on one side of the diaphragm substrate, the thickness of the lithium supplement coating is 1 to 5 μm; when the lithium supplement coating is disposed on both sides of the diaphragm substrate, the total thickness of the lithium supplement coating is 2 to 10 μm. The lithium supplement slurry is coated on the diaphragm substrate and dried at 30°C-80°C to obtain a lithium-ion battery diaphragm containing the lithium supplement coating.

[0049] The beneficial effects of the technical solution are: (1) applying the lithium replenishing coating to the lithium-ion battery separator, adopting the separator lithium replenishing method, introducing additional active lithium into the lithium battery, compensating for the irreversible capacity loss of active lithium in the initial stage and cycle process of the lithium battery;

[0050] (2) The application of the lithium supplement coating of the present invention is beneficial to enhancing the mechanical strength of the lithium battery separator, while improving the long-term wettability of the separator and improving safety;

[0051] (3) Compared with the positive / negative electrode lithium replenishment method, the diaphragm lithium replenishment can avoid the direct addition of lithium replenisher into the positive / negative electrode sheet, reduce the contact between the positive / negative electrode and the lithium replenisher, reduce the damage of the lithium replenisher decomposition to the positive / negative electrode structure, inhibit the catalytic decomposition of the electrode material such as FePO4 on the lithium replenisher, reduce the carbon residue after lithium replenishment, and have excellent electrochemical performance;

[0052] (4) The lithium replenishing coating of the present invention is applied to the lithium battery separator to replenish lithium continuously and stably, thereby effectively improving the energy density, long cycle life and stability of the lithium battery.

[0053] The present invention will be further described below through specific implementation modes. DETAILED DESCRIPTION

[0054] The advantages of the technical solution of the present invention are further compared and analyzed through the following examples and comparative examples.

[0055] Example 1

[0056] (1) Preparation of nanocarbon sources

[0057] a1. Dissolution-compounding: Use sulfonated asphalt powder with a thermal stability of 180°C as raw material and deionized water as solvent to dissolve and prepare a sulfonated asphalt aqueous solution with a solid content of 5%. Then add carbon nanotubes according to the compounding ratio of solid sulfonated asphalt powder to carbon nanotubes of 1:0.5, and obtain a compounded carbon source dispersion after high-speed dispersion and stirring for 2 hours;

[0058] a2. Sand milling: The carbon source dispersion prepared in step a1 is placed in a sand mill, and sand milled at a speed of 2500 r / min for 0.25 h using zirconium beads with a diameter of 0.25 mm as sand milling media to obtain a composite carbon source sand mill slurry;

[0059] a3. Purification: The composite carbon source sand-grinding slurry obtained in a2 is centrifuged using a sieve to collect the nano-carbon source purified liquid with a particle size D50 of 25 nm.

[0060] a4. Spray drying: Place the purified nano-carbon source solution obtained in step a3 into a spray dryer at 180° C. at a rate of 15 mL / min, and finally collect the nano-carbon source for later use.

[0061] (2) Preparation of lithium supplement materials

[0062] A lithium supplement consisting of an organic lithium salt and lithium carboxymethyl cellulose in a ratio of 1:0.025 is dissolved in deionized water, and stirred at room temperature for 2 hours at a stirring speed of 2500 r / min to prepare a 25% aqueous solution, i.e., a lithium supplement aqueous solution;

[0063] The prepared nanocarbon source was added to the lithium supplement aqueous solution at a ratio of 1:0.25, and stirred until the nanocarbon source was completely dispersed and dissolved, and then continued to stir and disperse for 2 hours to obtain a lithium supplement-nanocarbon source solution;

[0064] The lithium supplement agent-nano carbon source solution obtained above is slowly added into ethanol to recrystallize the lithium supplement agent to obtain a lithium supplement material.

[0065] (3) Preparation of phase change microcapsules

[0066] The mass ratio of organic phase change material, nano carbon source and nitrogen pyridine is 1:1:0.025;

[0067] First, a reactor capable of controlling pressure and temperature is used, 100 parts of a nano carbon source and 100 parts of an alkane phase change paraffin with a phase change temperature of 60°C are pre-added, then the temperature is raised to 60°C to completely dissolve the organic phase change material, and then supercritical carbon dioxide is introduced, and closed stirring is performed for 3 hours at a temperature of 80°C and a pressure of 20Mpa to fully mix the mixture, and the pre-expansion temperature is 40°C. Finally, 2.5 parts of a multifunctional nitrogen pyridine solution are quickly sprayed into the reactor nozzle, and after continued mixing and stirring for 1 hour, the temperature is lowered and the pressure is released at the same time to prepare nitrogen pyridine-modified phase change microcapsule nanopowder;

[0068] (4) Preparation of lithium replenishing slurry for lithium replenishing coating

[0069] In parts by weight, 20 parts of lithium supplement material, 30 parts of phase change microcapsules, 2 parts of polyvinylidene fluoride, and 500 parts of deionized water were taken, and the lithium supplement slurry was prepared by high-speed stirring at a stirring speed of 2500 r / min for 3 hours;

[0070] (5) Preparation of lithium-ion battery separators

[0071] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 5 μm, and the thickness of the double-sided lithium supplement coating was 10 μm.

[0072] Example 2

[0073] (1) Preparation of nanocarbon sources

[0074] a1. Dissolution-compounding: Using sulfonated asphalt powder with a thermal stability of 230°C as raw material and deionized water as solvent, a 30% solid content aqueous solution is prepared according to a compounding ratio of sulfonated asphalt powder to carbon nanotubes of 1:0.15, and a compounded carbon source dispersion is obtained after high-speed dispersion and stirring for 2 hours;

[0075] a2. Sand milling: The carbon source dispersion prepared in step (a1) is placed in a sand mill, and sand milled at a speed of 2500 r / min for 0.25 h using zirconium beads with a diameter of 0.25 mm as sand milling media to obtain a composite carbon source sand mill slurry;

[0076] a3. Purification: The above-mentioned composite carbon source sand-ground slurry is centrifuged using a sieve to collect the nano-carbon source purified liquid with a particle size D50 of 15 nm.

[0077] a4. Spray drying: Place the purified nanocarbon source solution obtained in step (a3) ​​into a spray dryer at 120° C. at a rate of 5 mL / min, and finally collect the nanocarbon source for later use.

[0078] (2) Preparation of lithium supplement materials

[0079] A lithium supplement consisting of an organic lithium salt Li2C4O4 and carboxymethyl cellulose lithium in a ratio of 1:0.005 is dissolved in deionized water, and stirred at room temperature at a stirring speed of 800 r / min for 6 hours to prepare a 10% aqueous solution, i.e., a lithium supplement aqueous solution;

[0080] The prepared nanocarbon source was added to the lithium supplement aqueous solution at a ratio of 1:0.05, and stirred until the nanocarbon source was completely dispersed and dissolved, and then continued to stir and disperse for 0.5 h to obtain a lithium supplement-nanocarbon source solution;

[0081] The lithium supplement agent-nano carbon source solution obtained above is slowly added into ethanol to recrystallize the lithium supplement agent to obtain a lithium supplement material.

[0082] (3) Preparation of phase change microcapsules

[0083] The mass ratio of organic phase change material, nano carbon source and nitrogen pyridine is 1:0.5:0.015;

[0084] First, a reactor capable of controlling pressure and temperature is used, 50 parts of a nano carbon source and 100 parts of an alkane phase change paraffin with a phase change temperature of 60°C are pre-added, and then the temperature is raised to 60°C to completely dissolve the organic phase change material, and then supercritical carbon dioxide is introduced, and closed stirring is performed for 3 hours at a temperature of 80°C and a pressure of 20Mpa to fully mix the mixture, and the pre-expansion temperature is 40°C. Finally, 1.5 parts of a multifunctional nitrogen pyridine solution are quickly sprayed into the reactor nozzle, and after continued mixing and stirring for 0.5 hours, the temperature is lowered and the pressure is released at the same time to prepare nitrogen pyridine-modified phase change microcapsule nanopowder;

[0085] (4) Preparation of lithium replenishing slurry for lithium replenishing coating

[0086] In parts by weight, 30 parts of lithium supplement material, 20 parts of phase change microcapsules, 10 parts of polyvinylidene fluoride, and 500 parts of deionized water were taken, and a lithium supplement slurry was prepared by high-speed stirring at a stirring speed of 2500 r / min for 3 hours;

[0087] (5) Preparation of lithium-ion battery separators

[0088] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 1.5 μm, and the thickness of the double-sided lithium supplement coating was 3 μm.

[0089] Comparative Example 1 (The process conditions are the same as those of Example 1, but the lithium supplement coating is not added with phase change microcapsules.)

[0090] (1) Preparation of nanocarbon sources

[0091] a1. Dissolution-compounding: Use sulfonated asphalt powder with a thermal stability of 180°C as raw material and deionized water as solvent to dissolve and prepare a sulfonated asphalt aqueous solution with a solid content of 5%. Then add carbon nanotubes according to the compounding ratio of solid sulfonated asphalt powder to carbon nanotubes of 1:0.5, and obtain a compounded carbon source dispersion after high-speed dispersion and stirring for 2 hours;

[0092] a2. Sand milling: The carbon source dispersion prepared in step (a1) is placed in a sand mill, and sand milled at a speed of 2500 r / min for 0.25 h using zirconium beads with a diameter of 0.25 mm as sand milling media to obtain a composite carbon source sand mill slurry;

[0093] a3. Purification: The above-mentioned composite carbon source sand-ground slurry is centrifuged using a sieve to collect the nano-carbon source purified liquid with a particle size D50 of 25 nm.

[0094] a4. Spray drying: Place the purified nanocarbon source solution obtained in step (a3) ​​into a spray dryer at 180° C. at a rate of 15 mL / min, and finally collect the nanocarbon source for later use.

[0095] (2) Preparation of lithium supplement materials

[0096] A lithium supplement consisting of an organic lithium salt and lithium carboxymethyl cellulose in a ratio of 1:0.025 is dissolved in deionized water, and stirred at room temperature for 2 hours at a stirring speed of 2500 r / min to prepare a 25% aqueous solution, i.e., a lithium supplement aqueous solution;

[0097] The prepared nanocarbon source was added to the lithium supplement aqueous solution at a ratio of 1:0.25, and stirred until the nanocarbon source was completely dispersed and dissolved, and then continued to stir and disperse for 2 hours to obtain a lithium supplement-nanocarbon source solution;

[0098] The lithium supplement agent-nano carbon source solution obtained above is slowly added into ethanol to recrystallize the lithium supplement agent to obtain a lithium supplement material.

[0099] (3) Preparation of lithium replenishing slurry for lithium replenishing coating

[0100] In parts by weight, 20 parts of lithium supplement material, 2 parts of polyvinylidene fluoride, and 500 parts of deionized water were taken, and the lithium supplement slurry was prepared by high-speed stirring at a stirring speed of 2500 r / min for 3 hours;

[0101] (4) Preparation of lithium-ion battery separators

[0102] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 5 μm, and the thickness of the double-sided lithium supplement coating was 10 μm.

[0103] Comparative Example 2 (The process conditions are the same as those of Example 1, but no lithium replenishing material is added to the lithium replenishing coating.)

[0104] (1) Preparation of nanocarbon sources

[0105] a1. Dissolution-compounding: Use sulfonated asphalt powder with a thermal stability of 180°C as raw material and deionized water as solvent to dissolve and prepare a sulfonated asphalt aqueous solution with a solid content of 5%. Then add carbon nanotubes according to the compounding ratio of solid sulfonated asphalt powder to carbon nanotubes of 1:0.5, and obtain a compounded carbon source dispersion after high-speed dispersion and stirring for 2 hours;

[0106] a2. Sand milling: The carbon source dispersion prepared in step (a1) is placed in a sand mill, and sand milled at a speed of 2500 r / min for 0.25 h using zirconium beads with a diameter of 0.25 mm as sand milling media to obtain a composite carbon source sand mill slurry;

[0107] a3. Purification: The above-mentioned composite carbon source sand-ground slurry is centrifuged using a sieve to collect the nano-carbon source purified liquid with a particle size D50 of 25 nm.

[0108] a4. Spray drying: Place the purified nanocarbon source solution obtained in step (a3) ​​into a spray dryer at 180° C. at a rate of 15 mL / min, and finally collect the nanocarbon source for later use.

[0109] (2) Preparation of phase change microcapsules

[0110] The mass ratio of organic phase change material, nano carbon source and nitrogen pyridine is 1:1:0.025;

[0111] First, a reactor capable of controlling pressure and temperature is used, 100 parts of a nano carbon source and 100 parts of an alkane phase change paraffin with a phase change temperature of 60°C are pre-added, then the temperature is raised to 60°C to completely dissolve the organic phase change material, and then supercritical carbon dioxide is introduced, and closed stirring is performed for 3 hours at a temperature of 80°C and a pressure of 20Mpa to fully mix the mixture, and the pre-expansion temperature is 40°C. Finally, 2.5 parts of a multifunctional nitrogen pyridine solution are quickly sprayed into the reactor nozzle, and after continued mixing and stirring for 1 hour, the temperature is lowered and the pressure is released at the same time to prepare nitrogen pyridine-modified phase change microcapsule nanopowder;

[0112] (3) Preparation of lithium replenishing slurry for lithium replenishing coating

[0113] In parts by weight, 30 parts of phase change microcapsules, 2 parts of polyvinylidene fluoride, and 500 parts of deionized water were stirred at a high speed of 2500 r / min for 3 hours to prepare a lithium supplement slurry;

[0114] (4) Preparation of lithium-ion battery separators

[0115] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 5 μm, and the thickness of the double-sided lithium supplement coating was 10 μm.

[0116] Comparative Example 3 (The process conditions are the same as those of Example 2, but the phase change microcapsules of the lithium supplement coating are not modified by nitrogen pyridine.)

[0117] (1) Preparation of nanocarbon sources

[0118] a1. Dissolution-compounding: Using sulfonated asphalt powder with a thermal stability of 230°C as raw material and deionized water as solvent, a 30% solid content aqueous solution is prepared according to a compounding ratio of sulfonated asphalt powder to carbon nanotubes of 1:0.15, and a compounded carbon source dispersion is obtained after high-speed dispersion and stirring for 2 hours;

[0119] a2. Sand milling: The carbon source dispersion prepared in step (a1) is placed in a sand mill, and sand milled at a speed of 2500 r / min for 0.25 h using zirconium beads with a diameter of 0.25 mm as sand milling media to obtain a composite carbon source sand mill slurry;

[0120] a3. Purification: The above-mentioned composite carbon source sand-ground slurry is centrifuged using a sieve to collect the nano-carbon source purified liquid with a particle size D50 of 15 nm.

[0121] a4. Spray drying: Place the purified nanocarbon source solution obtained in step (a3) ​​into a spray dryer at 120° C. at a rate of 5 mL / min, and finally collect the nanocarbon source for later use.

[0122] (2) Preparation of lithium supplement materials

[0123] A lithium supplement consisting of an organic lithium salt Li2C4O4 and carboxymethyl cellulose lithium in a ratio of 1:0.005 is dissolved in deionized water, and stirred at room temperature at a stirring speed of 800 r / min for 6 hours to prepare a 10% aqueous solution, i.e., a lithium supplement aqueous solution;

[0124] The prepared nanocarbon source was added to the lithium supplement aqueous solution at a ratio of 1:0.05, and stirred until the nanocarbon source was completely dispersed and dissolved, and then continued to stir and disperse for 0.5 h to obtain a lithium supplement-nanocarbon source solution;

[0125] The lithium supplement agent-nano carbon source solution obtained above is slowly added into ethanol to recrystallize the lithium supplement agent to obtain a lithium supplement material.

[0126] (3) Preparation of phase change microcapsules

[0127] The mass ratio of organic phase change material to nano carbon source is 1:0.5;

[0128] First, a reactor capable of controlling pressure and temperature is used, 50 parts of a nano carbon source and 100 parts of an alkane phase change paraffin with a phase change temperature of 60°C are pre-added, and then the temperature is raised to 60°C to completely dissolve the organic phase change material, and then supercritical carbon dioxide is introduced, and closed stirring is performed for 3 hours at a temperature of 80°C and a pressure of 20Mpa to fully mix the mixture, and the pre-expansion temperature is 40°C. Finally, the temperature is lowered and the pressure is released at the same time to prepare phase change microcapsule nanopowder;

[0129] (4) Preparation of lithium replenishing slurry for lithium replenishing coating

[0130] In parts by weight, 30 parts of lithium supplement material, 20 parts of phase change microcapsules, 10 parts of polyvinylidene fluoride, and 500 parts of deionized water were taken, and a lithium supplement slurry was prepared by high-speed stirring at a stirring speed of 2500 r / min for 3 hours;

[0131] (5) Preparation of lithium-ion battery separators

[0132] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 1.5 μm, and the thickness of the double-sided lithium supplement coating was 3 μm.

[0133] Comparative Example 4 (The process conditions are the same as those of Example 2, but no carbon source is added to the lithium-replenishing material of the lithium-replenishing coating and the phase-change microcapsules.)

[0134] (1) Preparation of lithium supplement materials

[0135] A lithium supplement consisting of an organic lithium salt Li2C4O4 and carboxymethyl cellulose lithium in a ratio of 1:0.005 is dissolved in deionized water, and stirred at room temperature at a stirring speed of 800 r / min for 6 hours to prepare a 10% aqueous solution, i.e., a lithium supplement aqueous solution;

[0136] The above lithium supplement aqueous solution is slowly added into ethanol to recrystallize the lithium supplement agent to obtain a lithium supplement material.

[0137] (2) Preparation of phase change microcapsules

[0138] The feeding mass ratio of organic phase change material to nitrogen pyridine is 1:0.015;

[0139] First, 100 parts of alkane phase change paraffin with a phase change temperature of 60°C are pre-added in a reactor capable of controlling pressure and temperature, and then the temperature is raised to 60°C to completely dissolve the organic phase change material, and then supercritical carbon dioxide is introduced, and closed stirring is performed for 3 hours at a temperature of 80°C and a pressure of 20Mpa to fully mix the mixture, and the pre-expansion temperature is 40°C. Finally, 1.5 parts of a multifunctional nitrogen pyridine solution are quickly sprayed into the reactor nozzle, and the mixture is continuously mixed and stirred for 0.5 hours, and then the temperature is reduced and the pressure is released to prepare nitrogen pyridine-modified phase change microcapsule nanopowder;

[0140] (3) Preparation of lithium replenishing slurry for lithium replenishing coating

[0141] In parts by weight, 30 parts of lithium supplement material, 20 parts of phase change microcapsules, 10 parts of polyvinylidene fluoride, and 500 parts of deionized water were taken, and a lithium supplement slurry was prepared by high-speed stirring at a stirring speed of 2500 r / min for 3 hours;

[0142] (4) Preparation of lithium-ion battery separators

[0143] The prepared lithium supplement slurry was coated on a separator substrate and dried at 50°C to obtain a lithium ion battery separator with a single-sided lithium supplement coating and a lithium ion battery separator with a double-sided lithium supplement coating, respectively. The thickness of the single-sided lithium supplement coating was 1.5 μm, and the thickness of the double-sided lithium supplement coating was 3 μm.

[0144] The following performance tests were performed on the samples of the above embodiments and comparative examples. The test methods and test results are as follows.

[0145] 1. Conductivity test

[0146] A PET substrate was selected as a lithium-ion battery separator substrate, and the lithium-replenishing slurry prepared by the process in Examples 1, 2 and Comparative Examples 1-4 was coated on the PET substrate. The wet film thickness was controlled by coating slit gap, and the lithium-replenishing coating was obtained by curing. The thickness was tested by a film thickness meter, and then the conductivity was tested by a four-probe tester.

[0147] The thickness of the lithium supplement coating was controlled to 5 μm, and the test results of the average resistivity are shown in Table 1:

[0148] Table 1 Test results of resistivity performance of lithium-supplemented coating

[0149] project Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Lithium supplement coating thickness (μm) 5 5 5 5 5 5 Average resistivity (Ω.cm) 0.43 0.49 0.57 0.64 0.63 Over range

[0150] It can be seen from Table 1 that the conductive properties of the lithium replenishing coatings in various embodiments are significantly different. The lithium replenishing agent is coated with a carbon source, and the phase change microcapsules are coated with a carbon source at the same time, so that the lithium replenishing material and the phase change material can be evenly dispersed and the compatibility is improved, thereby effectively improving the conductive properties of the lithium replenishing coating.

[0151] 2. Electrolyte immersion resistance test

[0152] The lithium-supplemented coated battery separators prepared in Examples 1, 2 and Comparative Examples 1-4 and the battery separator substrates without the lithium-supplemented coating were cut into square samples of 5 cm*5 cm, and then completely immersed in the electrolyte. After immersion for 24 hours, the appearance of the lithium-supplemented coating was observed. The results are shown in Table 2 (Lithium-ion Battery Separator Performance Test Results). The results in Table 2 show that the lithium-supplemented coating of the present invention is more resistant to immersion in the electrolyte, and no peeling, bulging, etc. occur after 24 hours.

[0153] 3. Diaphragm liquid absorption test

[0154] 3.1. The lithium-ion battery separators prepared in Examples 1, 2 and Comparative Examples 1-4 and the battery separator substrates without the lithium supplement coating were cut into separator samples to be tested with a size of 5 cm*10 cm respectively;

[0155] 3.2. Cut out two bare aluminum foils of the same shape as the diaphragm to be tested obtained in step 3.1 (length and width are 5 cm×10 cm), and sandwich the diaphragm to be tested between the two bare aluminum foils to form a sample to be tested;

[0156] 3.3. The test sample obtained in step 3.2 is hung vertically and placed in different temperature environments of 25°C, 45°C and 60°C, and placed in a container containing n-butanol solution, with one end of the test sample roll in contact with the test reagent and the other end away from the test reagent. The liquid absorption at different temperatures is allowed to stand for 1 hour to allow the test membrane to fully absorb the test reagent to a saturated state. Then, the test sample is taken out and the test reagent on its surface is gently wiped off, and the mass change of the battery membrane before and after the liquid absorption is recorded.

[0157] 3.4. Calculate the liquid absorption rate of the battery separator using the following formula:

[0158] Liquid absorption rate V (%) = [(M1-M0) / M0] × 100%, wherein M0 represents the mass of the membrane to be tested, and M1 represents the mass of the membrane after sufficient liquid absorption.

[0159] The test results are shown in Table 2 (Li-ion battery separator performance test results).

[0160] Table 2 Lithium-ion battery separator performance test results

[0161]

[0162] Analysis of the test results in Table 2 shows that: (1) the liquid absorption rates of Examples 1 and 2 are significantly greater than those of the bare diaphragm substrate and Comparative Examples 1-4, indicating that the electrolyte contact angle of the coated lithium supplement coating is smaller, which is more conducive to electrolyte infiltration and enhances the ability of the diaphragm to adsorb electrolyte, thereby improving the liquid absorption rate; (2) Under different temperature conditions, due to the addition of nano phase change microcapsules in the present application, phase change occurs with the change of temperature, thereby opening the pores on the surface of the battery diaphragm substrate containing the lithium supplement carbon coating layer, avoiding blockage of the diaphragm pores due to the lithium supplement coating; (3) The surface wettability of the battery diaphragm substrate is increased by adding an appropriate amount of lithium supplement material; (4) The addition of lithium supplement material and phase change microcapsules, the combination of the two, ultimately greatly improves the wettability of the battery diaphragm, thereby increasing the liquid absorption rate of the battery diaphragm for the electrolyte.

[0163] In Comparative Example 1, the lithium supplement coating is not added with phase change microcapsules, and the lithium supplement material alone cannot effectively increase the porosity of the battery separator matrix, resulting in a lower porosity of the separator and a lower liquid absorption rate of the electrolyte.

[0164] In Comparative Example 2, no lithium-supplementing material is added to the lithium-supplementing coating, and the coating is made only of phase change microcapsules. Since the phase change material cannot be well dispersed and evenly distributed, it is easy to stack up, which is not conducive to the uniform dispersion of the battery diaphragm matrix, and the wettability is poor and uneven, resulting in the pores of the final diaphragm being blocked, thereby reducing the liquid absorption rate of the diaphragm.

[0165] In Comparative Example 3, no multifunctional nitrogen pyridine was added. Due to the lack of multifunctional nitrogen pyridine as a cross-linking agent to react with the carboxyl-containing cross-linking reaction in the system, the carboxylmethyl cellulose-Li of the lithium supplement material in the system and the carboxyl groups in some binders cannot form a cross-linked network structure, resulting in slightly poor adhesion between the lithium supplement coating and the battery separator, resulting in the immersion bulging phenomenon.

[0166] In Comparative Example 4, no carbon source was added. The lithium replenisher Li2C2O4 and the phase change microcapsules without carbon source coating were used in the prepared lithium replenishing coating slurry. Due to their poor hydrophilicity, the lithium replenishing slurry was unevenly dispersed, which in turn led to poor uniformity of the lithium replenishing coating, poor wettability, and differences in the ability of the diaphragm to adsorb electrolyte, resulting in a not very obvious effect in improving the diaphragm's liquid absorption rate.

[0167] 4. Battery performance test

[0168] 4.1. Preparation and production of battery materials:

[0169] Preparation of diaphragm: The battery diaphragms containing lithium supplement coatings prepared in Example 1, Example 2 and Comparative Example 1-1, Comparative Example 1-2 and Comparative Example 1-3 are respectively used as battery diaphragms for battery installation;

[0170] Preparation of positive electrode sheet: according to the mass ratio of LiFePO4: PVDF: Super P = 96.5: 2.5: 1, add them into the organic solvent N-methylpyrrolidone, stir them thoroughly to obtain positive electrode slurry, apply it on aluminum foil, dry it and make it into positive electrode sheet;

[0171] Negative electrode sheet preparation: According to the mass ratio of graphite: SFG: Super P: CMC: SBR = 94.4: 1: 2: 1: 1.6, add deionized water, stir well to obtain negative electrode slurry, apply it on copper foil, and make negative electrode sheet after drying.

[0172] 4.2. Battery production and testing:

[0173] The vacuum dried electrode is made into a 18650 lithium-ion battery:

[0174] Formation: First, the battery is charged at a constant current of 0.02C for 4 hours; then the battery is charged at a constant current of 0.1C for 6 hours;

[0175] Capacity division: First, charge the battery at a constant current of 0.5C with a charge cut-off voltage of 4.1V, and then charge it at a constant voltage to a current of 0.03C; after leaving the battery for 10 minutes, discharge it at a constant current of 0.5C with a discharge cut-off voltage of 2.00V;

[0176] Cycle performance test: The battery is charged at a constant current of 0.5C rate, with a charging cut-off voltage of 4.1V, and then charged at a constant voltage to a current of 0.03C; after the battery is left for 10 minutes, it is discharged at a constant current of 0.5C rate, with a discharge cut-off voltage of 2.00V; after the battery is left for 10 minutes, it is charged at a constant current of 1.0C rate, with a cut-off voltage of 4.1V, and then charged at a constant voltage to a current of 0.03C; after the battery is left for 10 minutes, it is discharged at a constant current of 1.0C rate, with a discharge cut-off voltage of 2.00V. After the above 1C charge and discharge steps are cycled 500 times, the test is stopped. Record the data and calculate the initial discharge specific capacity, the first coulomb efficiency, and the capacity retention rate. The results are shown in Table 3.

[0177] Table 3 Battery performance test results

[0178]

[0179] The calculation method for the first coulombic efficiency is: the first discharge capacity after the capacity division is completed is divided by the sum of the formation charge capacity and the capacity division charge capacity.

[0180] From the analysis of Table 3, it can be seen that the discharge specific capacity and the first coulombic efficiency of Examples 1 and 2 provided in the present application are greater than those of Comparative Examples 1-4; and the retention rate of Example 1 after 500 cycles is still 96.6%, and the retention rate of Example 2 after 500 cycles is still 96.4%, which is significantly better than the blank group, that is, the battery made of a bare diaphragm substrate without a coating.

[0181] The above results fully demonstrate that the lithium replenishing coating of the present invention is applied to the battery separator. By pre-loading an excess of active lithium replenishing agent, under the synergistic effect of phase change microcapsules, the heat generated during the charging and discharging process of the lithium-ion battery is used to change the phase of the phase change material, so that the lithium replenishing coating produces a porous structure, which can not only provide a lithium source during the first charge, but also realize the continuous and stable release of active lithium.

[0182] After the battery separator is heated, the lithium ions in the lithium-replenishing coating on it slowly and continuously reach the negative and positive electrodes through the pores produced by phase change, effectively compensating for the lithium ions consumed in the early formation of the SEI film of the negative electrode material and the lithium ions consumed during the lithium battery cycle, thereby improving the initial coulombic efficiency and cycle life of the lithium battery.

Claims

1. A lithium supplement coating, comprising: Lithium replenishing materials, phase change materials and adhesives; Characterized in that the lithium supplement material comprises: a lithium supplement agent and a carbon source for the lithium supplement material coated on the lithium supplement agent; The lithium supplement comprises: x C y O z Organic lithium salt, structural formula Li x C y O z Medium: 1<X<5, 0<Y<8, 2<Z<12; The carbon source for lithium supplementing material is a carbon source capable of improving the conductivity of the lithium supplementing material; The mass ratio of the lithium supplement agent to the carbon source for the lithium supplement material is: 1:(0.05-0.25).

2. A lithium supplement coating according to claim 1, characterized in that: In parts by weight, the lithium replenishing coating comprises: 20-30 parts of lithium replenishing material, 10-20 parts of phase change material and 2-10 parts of adhesive.

3. A lithium supplement coating according to claim 1, characterized in that: The lithium supplement agent further comprises: a lithium supplement agent auxiliary dispersant; the lithium supplement agent auxiliary dispersant is: lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose; the mass ratio of the organic lithium salt to the lithium supplement agent auxiliary dispersant is 1:(0.005-0.025).

4. A lithium supplement coating according to claim 1, characterized in that: The organic lithium salt is one or more of Li2C2O4, Li2C4O4, Li2C3O5, Li2C4O6, and Li2C6O6.

5. A lithium supplement coating according to claim 1, characterized in that: The phase change material is: a phase change microcapsule with a core-shell structure, the phase change microcapsule comprises: an organic phase change material with a phase change temperature of 25-60°C and a carbon source for the phase change material coated on the organic phase change material; The carbon source for phase change material is a carbon source that can improve the conductivity of the phase change material; The mass ratio of the organic phase change material to the carbon source for the phase change material is 1:(0.5-1).

6. A lithium supplement coating according to claim 5, characterized in that: The phase change microcapsules are nitrogen pyridine modified phase change microcapsules; in the nitrogen pyridine modified phase change microcapsules, the mass ratio of organic phase change material, carbon source for phase change material and nitrogen pyridine is: 1:(0.5-1):(0.015-0.025).

7. A lithium supplement coating according to claim 1 or 5, characterized in that: The carbon source for lithium supplement material and / or the carbon source for phase change material is: a carbon source containing sulfonic acid groups; And / or the carbon source for lithium supplement material and / or the carbon source for phase change material is: a carbon source with a particle size D50 of nanometer level.

8. A lithium supplement coating according to claim 7, characterized in that: The carbon source for lithium supplement material and / or phase change material is a carbon source prepared by compounding an organic carbon source containing sulfonic acid groups and carbon nanotubes in a ratio of 1: (0.15-0.5).

9. A method for preparing a lithium supplement coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1, preparing the lithium supplement material; S2, preparing the phase change material; S3, mixing the lithium supplement material obtained in step S1, the phase change material obtained in step S2, a binder and a solvent, and stirring at high speed to obtain a lithium supplement slurry; S4, coating the lithium supplement slurry obtained in step S3 on the lithium supplement coating carrier, and obtaining the lithium supplement coating after drying; In the step S1, the lithium supplement material is prepared by the following steps: S1.1, preparing the carbon source for the lithium supplement material; S1.2, preparing a lithium supplement solution containing a lithium supplement agent; S1.3, adding the carbon source for lithium supplementing material obtained in step S1.1 to the lithium supplementing solution containing the lithium supplementing agent in step S1.2, stirring to disperse and dissolve the carbon source for lithium supplementing material, to obtain a lithium supplementing agent-lithium supplementing material carbon source solution; S1.4, recrystallizing the lithium supplement in the lithium supplement-lithium supplement material carbon source solution obtained in step S1.3 to obtain a lithium supplement-lithium supplement material carbon source composite material, namely, the lithium supplement material.

10. The method for preparing a lithium supplement coating according to claim 9, characterized in that: In the step S1.2, a lithium supplement solution containing a lithium supplement agent is prepared by the following method: an organic lithium salt and a lithium supplement agent auxiliary dispersant are taken in a ratio of 1: (0.005-0.025), dissolved in water, and prepared into a lithium supplement solution containing a lithium supplement agent with a concentration of 10-25%; And / or in step 3, the lithium supplement slurry comprises, by weight: 20 to 30 parts of lithium supplement material, 10 to 20 parts of phase change material, 2 to 10 parts of binder and 300 to 500 parts of solvent; And / or in the step S2, the phase change material is prepared by using supercritical fluid technology, and the preparation method includes the following steps: S2.1, adding an organic phase change material and a carbon source for phase change material into a pressure and temperature controllable reactor, heating the organic phase change material to melt; then introducing a supercritical fluid reaction medium, at 40-80°C and a pressure of 7.5-20 MPa, to obtain a phase change microcapsule suspension of the organic phase change material coated with the carbon source for phase change material; S2.

2. Prepare the desired phase-change microcapsules by using the phase-change microcapsule suspension obtained in step S2.1 through the method of step S2.2.1 or S2.2.2: The step S2.2.1 is: subjecting the phase change microcapsule suspension obtained in step S2.1 to rapid cooling and pressure relief to obtain phase change microcapsule powder; The step S2.2.2 is as follows: spraying the multifunctional nitrogen pyridine solution into the phase change microcapsule suspension obtained in step S2.1, stirring and mixing, rapidly cooling and releasing the pressure to obtain nitrogen pyridine-modified phase change microcapsules.

11. A lithium ion battery separator, characterized in that: The lithium-ion battery separator comprises: a separator substrate and a lithium supplement coating arranged on one side or both sides of the separator substrate; The lithium-replenishing coating is the lithium-replenishing coating according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative lithium supplement pole piece and preparation method and application thereof

    CN115036507A